1999
DOI: 10.1093/jee/92.5.1014
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition by European Corn Borer (Lepidoptera: Crambidae) in Response to Various Transgenic Corn Events

Abstract: Oviposition preference by European corn borers, Ostrinia nubilalis (Hübner), for or against transgenic corn would influence amounts of refuge required for resistance management. The objective of this research was to determine if various Bacillus thuringiensis (Bt) corn transgenic events influence O. nubilalis oviposition. All commercially available events (currently 5) were evaluated, plus 1 experimental event. Results from 3 independent studies are reported, including 3 field-cage experiments with vegetative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 11 publications
3
24
1
4
Order By: Relevance
“…These results provide further evidence that H. zea has no oviposition preference between Bt and non-Bt plants (Yang et al, 2014b). Similarly, indiscriminate oviposition behavior between Bt and non-Bt plants has also been shown in several other target species of Bt crops; including European corn borer, Ostrinia nubilalis (Hübner), pink bollworm, Pectinophora gossypiella, and cotton bollworm, Helicoverpa armigera (Orr and Landis, 1997;Hellmich et al, 1999;Hutchison et al, 2010;Liu et al, 2002;Fig. 3.…”
Section: Discussionsupporting
confidence: 57%
“…These results provide further evidence that H. zea has no oviposition preference between Bt and non-Bt plants (Yang et al, 2014b). Similarly, indiscriminate oviposition behavior between Bt and non-Bt plants has also been shown in several other target species of Bt crops; including European corn borer, Ostrinia nubilalis (Hübner), pink bollworm, Pectinophora gossypiella, and cotton bollworm, Helicoverpa armigera (Orr and Landis, 1997;Hellmich et al, 1999;Hutchison et al, 2010;Liu et al, 2002;Fig. 3.…”
Section: Discussionsupporting
confidence: 57%
“…It seems that it is important for the neonates to have the ability to assess host quality to be successful on a suitable host. Hellmich et al (1999) showed that ovipositing female European corn borer moths cannot detect Bt plants and the females have no differences in their oviposition frequency between Bt and non-Bt isoline corn. Therefore, when an egg mass is deposited on a corn plant, the neonate is the key developmental stage in determining host acceptance in Bt corn.…”
Section: Table 2 Mean ؎ Sd Number (Mean Percentage) Of Neonates Recomentioning
confidence: 99%
“…However, there is little documentation to state this with certainty. Hellmich et al (1999) concluded that ovipositing females are not able to distinguish between various Bt varieties and their respective near-isogenic varieties. The general consensus seems to be that the lepidopteran targets of Bt cannot detect it until larvae have ingested the toxins, and the toxins have bound to the receptor sites in the gut (Sutherland et al 2003).…”
mentioning
confidence: 99%
“…Transgenic insecticidal plants represent a novel method of insecticide delivery and relatively little is known regarding the ability of insects to detect or avoid the toxins produced by these plants (Hellmich et al 1999). Because the toxins produced by transgenic insecticidal plants are very speciÞc and bound within the plant tissues, they are generally considered to cause little or no impact on nontarget organisms (Ostlie et al 1997).…”
mentioning
confidence: 99%